Firm, yet flexible: a fidelity debate paper with two case examples - Bianca Albers; Lotte Verweij; Kathrin Blum; Saskia Oesch; Marie-Therese Schultes; Lauren Clack; Rahel Naef (Implementation Science)
Abstract Background In healthcare research and practice, intervention and implementation fidelity represent the steadfast adherence to core components of research-supported interventions and the strategies employed for their implementation. Evaluating fidelity involves determining whether these core components were delivered as intended. Without fidelity data, the results of complex interventions cannot be meaningfully interpreted. Increasingly, the necessity for firmness and strict adherence by implementers and their organizations has been questioned, with calls for flexibility to accommodate contextual conditions. This shift makes contemporary fidelity a balancing act, requiring researchers to navigate various tensions. This debate paper explores these tensions, drawing on experiences from developing fidelity assessments in two ongoing effectiveness-implementation hybrid trials. Main body First, given often scarce knowledge about the core components of complex interventions and implementation strategies, decisions about fidelity requirements involve a degree of subjective reasoning. Researchers should make these decisions transparent using theory or logic models. Second, because fidelity is context-dependent and applies to both interventions and implementation strategies, researchers must rethink fidelity concepts with every study while balancing firmness and flexibility. This is particularly crucial for hybrid studies, with their differing emphasis on intervention and implementation fidelity. Third, fidelity concepts typically focus on individual behaviors. However, since organizational and system factors also influence fidelity, there is a growing need to define fidelity criteria at these levels. Finally, as contemporary fidelity concepts prioritize flexible over firm adherence, building, evaluating, and maintaining fidelity in healthcare research has become more complex. This complexity calls for intensified efforts to expand the knowledge base for pragmatic and adaptive fidelity measurement in trial and routine healthcare settings. Conclusion Contemporary conceptualizations of fidelity place greater demands on how fidelity is examined, necessitating the expansion of fidelity frameworks to include organizational and system levels, the service- and study-specific conceptualizations of intervention and implementation fidelity, and the development of pragmatic approaches for assessing fidelity in research and practice. Continuing to build knowledge on how to balance requirements for firmness and flexibility remains a crucial task within the field of implementation science.